2017
DOI: 10.1089/chi.2016.0199
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Loss of Control Eating and High-Sensitivity C-Reactive Protein Concentrations

Abstract: Background: Loss of control (LOC) eating in youth is associated with excess body weight and adiposity. After adjusting for fat mass, youth with LOC eating have higher blood pressure and higher low-density lipoprotein cholesterol compared to youth without LOC eating. Increased inflammation may account for this relationship, although few data have examined this hypothesis. Therefore, this study explored the association between LOC eating and high-sensitivity C-reactive protein (hsCRP), a marker of inflammation.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 75 publications
1
17
0
Order By: Relevance
“…Indeed, prior studies show that snack intake better distinguishes youth with LOC eating from youth without LOC eating than total intake [14, 15], and may account for the associations between LOC eating and metabolic syndrome components [10] and C-reactive protein, a measure of chronic inflammation [9]. Thus, impacting dessert and snack food intake, specifically, may be an important target of excess weight gain prevention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, prior studies show that snack intake better distinguishes youth with LOC eating from youth without LOC eating than total intake [14, 15], and may account for the associations between LOC eating and metabolic syndrome components [10] and C-reactive protein, a measure of chronic inflammation [9]. Thus, impacting dessert and snack food intake, specifically, may be an important target of excess weight gain prevention.…”
Section: Discussionmentioning
confidence: 99%
“…The endorsement of recent LOC eating is associated with greater depressive and anxiety symptoms [24], lower self-esteem [5, 6], higher likelihood of overweight and obesity [7], more physiological markers of stress [8, 9], and a greater odds of presenting with components of the metabolic syndrome [10]. Of particular concern are data demonstrating that LOC eating places youth at undue risk for excess weight and fat gain [11, 12] and exacerbation of metabolic syndrome components [13].…”
Section: Introductionmentioning
confidence: 99%
“…youth (Shank et al, 2017) who report LOC eating have increased markers of inflammation relative to their peers. It is important for future research to examine how LOC eating impacts specific components of metabolic health.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that LOC eating impacts cardiometabolic health through nonspecific pathways, such as inflammation. Cross‐sectional analyses have shown that adults (Succurro et al, ) and youth (Shank et al, ) who report LOC eating have increased markers of inflammation relative to their peers. It is important for future research to examine how LOC eating impacts specific components of metabolic health.…”
Section: Discussionmentioning
confidence: 99%
“…All-in-all, it is intriguing to note that independent sources have now pinpointed that easy access to hyper-caloric/ industrially manipulated food has posed the basis for the rise of childhood obesity. This early pathologic weight gain, in turn, has been recognized as the one factor in the increase of the inflammatory tune [71], a chronic bias that seems to pervade us since early in life. Indeed, this inflammatory background might be the reason to thrive for IBD and the tens of the inflammatory "Western" disorders named above These profound changes, as expected, have significantly impacted our overwhelming microbiome population, which, as emphasized above, crowds our gut with some 10 4 microbic individuals.…”
mentioning
confidence: 99%